The experiences of therapy from the perspectives of carers of people with dementia: An exploratory study. Issue 1 (11th February 2014) - Elvish, Ruth; Cawley, Rosanne; Keady, John
Abstract : Design: Interviews were conducted with six carers of people with dementia about their experience of receiving counselling/psychotherapy. Interviews were conducted in the carer's own home, and data were analysed thematically using a narrative approach. Findings: Three themes were identified from the data: 'Still doing the best I can' (identified as losses and processes of personal growth); 'Feeling connected and being understood' (identified as attributes believed to be important within the therapeutic relationship); and 'Wanting to share information' (identified as sharing information with someone 'neutral'). Carers placed emphasis on the age of the therapist and the amount of therapist self‐disclosure. Attending counselling and/or psychotherapy also helped the carer to find a 'safe space' to disclose and share concerns. Discussion: Carer loss and personal growth are explored, together with the importance of building therapeutic relationships and, for the therapist, seeking supervision when managing personal self‐disclosure. The theme of therapist self disclosure is explored together with the importance of therapists seeking supervision when managing personal self‐disclosure.